ESRA19-0478 A quality improvement project assessing postoperative pain relief in paediatric patients undergoing lower limb osteotomy. (30th August 2019) - Mistry, V; Errico, M; Danha, R; Chari, S; Maxwell, H
Abstract : Background and aims: We assessed the effectiveness of intra-operative analgesic techniques for paediatric patients undergoing lower limb osteotomy. The project was registered with our audit department and further ethical approval was not required. Methods: The project was a retrospective case-note review over 18 months. All patients receive regular Paracetamol and Ibuprofen and Morphine and Ketamine nurse-controlled analgesia (NCA) on paediatric HDU. We discovered that pain scores in paediatric HDU were assessed using a 0 –3 scale; 0 –no pain, 3 –severe pain. Results: We identified 23 patients; 22 patients received caudal anaesthesia and 1 patient received peripheral nerve block. 16 of the 22 caudal patients received Clonidine. The percentage of patients who were pain free at 6 hours were: Clonidine >2μg/kg: 100%, Clonidine <2μg/kg: 36% and no Clonidine: 83%. We found no correlation between the dose of Levobupivacaine in mg/kg and pain scores at 6, 24 and 48 hours. The peripheral nerve block patient was pain free at 6, 24 and 48 hours. All patients were pain free at 48 hours irrespective of intra-operative analgesic technique. Conclusions: We demonstrated that caudals with a dose of clonidine >2 μg/kg lead to complete pain relief at 6 hours postoperatively. We recommend that regional anaesthesia is required for paediatric lower limb osteotomy, and if caudal anaesthesia is used a dose of Clonidine > 2μg/kg should be used. 1 We also recommend assessing pain score more accurately through using validated methods, such as FLACC or Wong-Baker FACES which will accommodate assessing pain scores more accurately. 2